Clara Louisa Penney, The book called "Celestina" in the Library of The Hispanic Society of America. New York, 1954; viii + 157 pp., ilustr. - Serís, Homero (El Colegio de México, 2007)
Se reseñó el libro: The book called "Celestina" in the Library of The Hispanic Society of America.